Language Styles Used in Jete Indonesia and Doran Gadget’s article - Filippo Aurel Kezia (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study aims to examine the language style used in an article of Jete Indonesia which is Five Best Jete Smartwatches to Accompany Your Activity, and Doran Gadget’s article which is GoPro Hero Twelve Specifications: Longer Battery Life!. The objective of the study is to analyze the different and similar language styles that were used in Jete Indonesia's article and Doran Gadget’s article. Besides, the writer employs a descriptive qualitative approach using Keraf’s (2010) theory on the types of language styles based on diction. The data analysis shows there is not a significant difference in the language styles used in Jete Indonesia’s article and Doran Gadget’s article. The research findings could be indicated by the vocabulary used in the formal and informal language styles from Jete Indonesia’s article and Doran Gadget’s article. Concerning the conversational style used between Jete Indonesia and Doran Gadget’s article, Doran Gadget which is a formal style employs the conversational style more than Jete Indonesia which is an informal one.